External Environment, Enabling Factors and Predisposing Characteristics of Fully Immunised Children in Nepal - Thapa, Kanchan; Suwal, Bhim Raj; Adhikary, Pratik (Journal of Nepal Paediatric Society, 2019)
Introduction: Immunisation is a cost-effective public health intervention worldwide responsible for the reduction of infant and child morbidity and mortality. Full immunisation is a state of obtaining all vaccination according to the Immunisation schedule of Nepal. Methods: The secondary data of Nepal was downloaded from the DHS Program. A total of 1709 children aged 16-23 months were analysed for descriptive statistics. All the analyses were weighted by its sampling weight. The full immunisation status indicates those who completed 1 dose of BCG, 3 doses of Polio, 3 doses of DPT and 1 dose of Measles. The independent variables are further subdivided into enabling, predisposing and external environmental factors. Results: Over half of children (52.6%) were from Terai, nearly a quarter (23.0%) from province 2. More males (53.5%) and the majority of (86.1%) children with birth order one to three were immunised. Mother aged < 20 years (62%), working father (96.1%), working mother (59.7%), educated father (87.3%) and educated mother (70.7%) had children with complete immunisation. Non-smoker mother (94.6%) had fully immunised children. Nearly three quarters (73.5%) from a middle and rich family, those with PNC within 3 days (35.9%), delivered at a health facility (64.2%), and had PNC check from the skilled provider (12.1%) had completely immunised their children. Conclusions: Significant differences based on external environment, enabling factors and predisposing factors for full immunisation status was observed. Specific interventions based on these factors are recommended.